2007
DOI: 10.1044/1092-4388(2007/067)
|View full text |Cite
|
Sign up to set email alerts
|

The Language Experience and Proficiency Questionnaire (LEAP-Q): Assessing Language Profiles in Bilinguals and Multilinguals

Abstract: The LEAP-Q is a valid, reliable, and efficient tool for assessing the language profiles of multilingual, neurologically intact adult populations in research settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
1,068
0
14

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,470 publications
(1,185 citation statements)
references
References 66 publications
18
1,068
0
14
Order By: Relevance
“…Their language profile was determined via the Dutch version of LEAP-Q (Marian, Blumenfeld, & Kaushanskaya, 2007). Two (one Switching and one NonSwitching participant) were exposed to both Dutch and English from an early age (< 4).…”
Section: Methods Participantsmentioning
confidence: 99%
“…Their language profile was determined via the Dutch version of LEAP-Q (Marian, Blumenfeld, & Kaushanskaya, 2007). Two (one Switching and one NonSwitching participant) were exposed to both Dutch and English from an early age (< 4).…”
Section: Methods Participantsmentioning
confidence: 99%
“…Excluding these five participants did not change the overall pattern of results and they are therefore included in the analyses reported below. Thirty-eight participants (42%) spoke more than one language with at least adequate proficiency (as assessed by the LEAP-Q; Marian, Blumenfeld, & Kaushanskaya, 2007; see below for details) and an additional 19 (20%) reported minimal proficiency in a language other than English. Eight participants were left-handed (i.e., had negative scores on the Edinburgh 1 One additional reason not to rely on group assignment is that our participants did not appear to have been overly concerned about meeting group criteria; e.g., eleven participants who responded to the 'musician' recruitment ads later reported having had between 0-5 years of music lessons.…”
Section: Participantsmentioning
confidence: 99%
“…Given evidence (albeit mixed) for a greater prevalence of lefthandedness in musicians (Aggleton, Kentridge, & Good, 1994), handedness effects on musical ability (e.g., Kopiez, Galley, & Lee, 2006;Jäncke, Schlaug, & Steinmetz, 1997), and handedness effects on cognitive tasks (also with somewhat mixed findings; e.g., Beratis, Rabavilas, Kyprianou, Papadimitriou, & Papageorgiou, 2013;Nettle, 2003;Powell, Kemp, & García-Finaña, 2012), we administered the Edinburgh handedness inventory (Oldfield, 1971). Finally, bilingualism has been found to predict aspects of EF (e.g., Bialystok, Craik, Green, & Gollan, 2009), so we administered the Language Experience and Proficiency Questionnaire (LEAP-Q; Marian et al, 2007): participants were considered bilingual if they reported speaking a second language with a mean self-rated proficiency of at least 5 on a 1 to 10 scale (where 5 is defined as "adequate"), averaged across ratings of ability in second language speaking, understanding, and reading.…”
Section: Other Background and Demographic Measuresmentioning
confidence: 99%
“…One subject (Spanish-dominant) was eliminated for failing to complete all parts of the task. Each participant's language background was assessed using a modified version of the LEAP-Q (Marian, Blumenfeld & Kaushanskaya 2007) and relied on self-ratings, which have been shown to be an accurate representations of linguistic performance in bilingual speakers (Chincotta & Underwood 1998, Flege, Yeni-Komshian & Liu 1999, Jia, Aaronson & Wu 2002. The language background questionnaires were prepared in both English and Spanish, and participants were free to choose their preferred version.…”
Section: Participantsmentioning
confidence: 99%